Sustainable Operations Management. - Brown, Steve, 1957- (International Journal of Operations & Production Management: Volume 34, Issue 5., 2014)
Increasingly, organisations are interested in managing corporate social responsibility (CSR) and sustainability as part of their operations management (OM). OM practices and research must respond to demands to address sustainability. This response is triggered by climate change and other environmental concerns, the well-being of workers and communities, and other broad social demands. We define sustainable OM as the pursuit of social, economic and environmental objectives - the triple bottom line [TBL] - within operations of a specific firm and operational linkages that extend beyond the firm.